2002
DOI: 10.1109/8.999618
|View full text |Cite
|
Sign up to set email alerts
|

Application of a microgenetic algorithm (MGA) to the design of broadband microwave absorbers using multiple frequency selective surface screens buried in dielectrics

Abstract: Over the years, frequency selective surfaces (FSSs) have found frequent use as radomes and spatial filters in both commercial and military applications. In the literature, the problem of synthesizing broadband microwave absorbers using multilayered dielectrics through the application of genetic algorithms (GAs) have been dealt with successfully. Recently, spatial filters employing multiple, freestanding, FSS screens have been successfully designed by utilizing a domain-decomposed GA. In this paper, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(67 citation statements)
references
References 11 publications
0
63
0
4
Order By: Relevance
“…This bandwidth is unique among all the designs ever published [2,3,8,10,1416]. It is shown that the total thickness of the design (14.5 mm) is only 0.7% thicker than the minimum possible thickness dictated by the physical bound.…”
Section: Introductionmentioning
confidence: 92%
“…This bandwidth is unique among all the designs ever published [2,3,8,10,1416]. It is shown that the total thickness of the design (14.5 mm) is only 0.7% thicker than the minimum possible thickness dictated by the physical bound.…”
Section: Introductionmentioning
confidence: 92%
“…7 Recent advances in FSS include the use of genetic algorithms and Pareto optimizations to synthesize broadband, multilayer FSS. 8 These FSS have been used in designs for a considerable time and have been quite successful. However, due to their periodic structure and structures comparable to wavelength, challenges remain with unwanted passbands, off-normal incidence, and polarizations.…”
Section: Introductionmentioning
confidence: 99%
“…Since, the amount of energy lost or energy absorbed by the patch array is evaluated based on the value of R s , it is important to determine the right value of R s in designing wideband absorbers. The most common way is to use numerical optimization techniques such as [27,28], among others. However, discussion of these techniques is beyond the scope of this work.…”
Section: Single-layer Mushroom His Structure With Thin Resistive Patchesmentioning
confidence: 99%